Tax Policy Handbook. (International Monetary Fund, 1995)
Edited by Parthasarathi Shome, this Handbook was written primarily for economists who are responsible for analyzing and evaluating economic policies of developing countries at an applied level, and who would benefit from a comprehensive discussion of the concepts, principles, and prevailing issues of taxation.